Kemajuan Islam pada Masa Kekaisaran Turki Utsmani - Mami Nofrianti; Kori Lilie Muslim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This paper discusses the progress of Islam in the Ottoman Empire. The purpose of this paper is to describe how progress has been made for the progress of the Ottoman Turks in the development of Islam. The problem to be answered in this paper is: What is the background of the emergence of the Ottoman government and the progress achieved by the Ottoman Empire. This writing uses a historical approach, with descriptive analysis method. In this paper, it is found that the background of the emergence of the Ottoman government began with the return of Sultan Ala ad-Din II from the Seljuq Rum Ertoghul who led the army against the Roman army and then won. With this victory, Sultan Ala ad-Din gave Erthogul a gift, an area bordering Byzantium. Then he built the land and expanded his territory to Byzantium. Erthogul had a child named Usman who was born in 1258 AD That Usman name was taken as the name of the Ottoman Empire. The progress achieved by the Ottoman Empire included developments in the field of thought in the military and government fields, as well as in the fields of science and culture, as well as in the religious fields